KERATON KUSUMA NEGARA SEBAGAI MEDIA PEMBELAJARAN SEJARAH DI SMA NEGERI 1 SEKADAU - Diki Ilham Riyadi; Agus Sastrawan Noor; Andang Firmansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis study aim to find out the evidences of the Keraton Kusuma Negara that could be used as a learning medium and also to find out how to use it and the obstacles in utilizing the Keraton Kusuma as a medium of historical learning at SMA Negeri 1 Sekadau. Researcher using descriptive methods using a qualitative approach. The subjects of this study was 8 people with 1 person in charge of Keraton Kusuma Negara, 1 history teacher, and 6 students of class XI IPS.Techniques used in data collection include observation, interviews, and documentation. The results showed that there are 3 relics that can be used as a medium of learning history, then teachers using Keraton Kusuma Negara by presenting photos to students when learning materials take place so that they can understand the history of Keraton Kusuma Negara. The obstaclesarise when technical problems such as power failure and lack of projectors as well as very limited resource constraints when the teacher present them in class, where the teacher anticipating technical problem by printing the photo and showing it to the class, then anticipating limited resource constraint by searching for related literature.Keywords: Historical Learning, Historical Learning Media, Keraton Kusuma Negara